(untitled) (Journal of Information Technologies in Education (ITE), 2015)
The effective tool of quality control the standardization is which includes a set of rules,regulations and requirements for product quality. The development and adoption of international standards in the field of ICT in order to ensure their quality is an integral part of the process of building the information society. The introduction of high-quality, open, interoperable and standards-related demand, which takes into account the requirements and needs of all stakeholders, is now a key element of development and diffusion of ICT, streamlining costs for their development and improvement, which is particularly important for countries with transition economies. In the article the necessity of standardizing of the requirements to ICT of educational purposes is grounded. The basic types of documents on technical regulation and standardization are represented. The activities of leading international and regional initiatives and organizations whose activities, among other things, aims to standardize requirements to educational ICT (ISO, CEN,IEEE, IMS, ADL), and their main projects, are reflected. The local problems and achievements in this field are outlined. The aim of the paper is to reflect international experience in the standardization of the requirements for educational ICT, in view of globalization and integration processes.